KRISIS PADA TAHAP AWAL PASCA-PERKAWINAN KATOLIK DAN UPAYA MENGATASI KRISIS BERDASARKAN SURAT APOSTOLIK AMORIS LAETITIA - Monteiro, Yohanes Hans; Kleden, Fransiskus Bala; Ture, Gergorius; Pasaribu, Astina Vebriani; Situmorang, Vinsensius M. Junior (Bahasa Indonesia, 2024)
In the Catholic Church, the reality of married life shows that various kinds of crises come and disrupt the lives of married couples during the early stages of catholic post-marriage. The focus of this article is to elaborate crisis during the early stages of Catholic post-marriage and attempts to address the crisis. Therefore, this article reviews the Apostolic Exhortation Amoris Laetitia from Pope Francis which speaks about Catholic marriage as the guidance for dealing with the crisis. The authors use the method of interview and literature study. In the interview method, the authors interview key informants who talk about problems during the early stages of catholic post-marriage. This study found that crisis during the early stages of catholic post-marriage is characterized by four main reasons, namely the necessity to leave parents, adjustment to one’s partner, the presence and care of children, and the presence of elderly parents. Dealing with these problems, the Church through its family pastoral inspired by the Amoris Laetitia comes to provide spiritual, moral and practical supports to the families in order to face the crises. The Church must be alert in designing programs and activities such as recollections, retreats, group discussions, family visits, and so on which are useful for strengthening family resilience and strengthening their family building and integrity.